The Optimum Field Configuration for Active MASW Survey on Peat Soil - Abu Talib, Mohd Khaidir; Basri, Kasbi; Zainorabidin, Adnan; Wahab, Haliza (International Journal of Integrated Engineering, 2020)
The application of the MASW method on engineering investigation required optimization of the field configuration to ensure high quality dispersion image for reasonable shear wave velocity profile estimation. The limited investigation with respect to peat soil condition has motivated the study to determine the optimum field configuration for peat soil. The challenging characteristics of peat soil including high void ratio, compressibility, water content and low shear strength further complicates the determination of optimum field configurations. The study focused on the determination of optimum field configurations for active MASW method which includes the receiver spacing, source offset, sensor frequency and sampling interval. The results obtained shows that, the optimum receiver spacing to obtain high signal to noise ratio dispersion image was 1 meter. Smaller receiver spacing causes domination of higher modes and wide bandwidth, while longer receiver spacing causes significant drop in signal to noise ratio governed by rapid energy dissipation with distance. For the source offset, the distance of half the total spread length (X1 = L/2) provides the best resolution and minimised near-field and far-field effect. While, 4.5 Hz sensor frequency and sampling interval between 100 to 250 ms provides sufficient low frequencies for deeper depth investigation and denser data. Overall, the influence of receiver spacing, source offset and sensor frequency on the dispersion image resolution was significant.